2017
DOI: 10.1155/2017/2542950
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Content of Sulfate Groups in Seaweed Polysaccharides on Antioxidant Activity and Repair Effect of Subcellular Organelles in Injured HK‐2 Cells

Abstract: This study aims to investigate the repair effect of subcellular structure injuries of the HK-2 cells of four degraded seaweed polysaccharides (DSPs), namely, the degraded Porphyra yezoensis, Gracilaria lemaneiformis, Sargassum fusiform, and Undaria pinnatifida polysaccharides. The four DSPs have similar molecular weight, but with different content of sulfate groups (i.e., 17.9%, 13.3%, 8.2%, and 5.5%, resp.). The damaged model was established using 2.8 mmol/L oxalate to injure HK-2 cells, and 60 μg/mL of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 47 publications
2
27
0
1
Order By: Relevance
“…Noticeably, there was a double increase in the OH • scavenging ability from 46.03 % to 95.24 % between EPS and S-EPS11. The results strongly agree with Ma et al reported that antioxidant activity of sulfated polysaccharides were correlated with increasing sulfate contents and DS of products [10]. Collectively, our results revealed that the sulfated EPS reliably increase the bio-activities of EPS extracted from O. sinensis culture broth.…”
Section: Antioxidant Of Sulfated Eps From O Sinensissupporting
confidence: 92%
See 1 more Smart Citation
“…Noticeably, there was a double increase in the OH • scavenging ability from 46.03 % to 95.24 % between EPS and S-EPS11. The results strongly agree with Ma et al reported that antioxidant activity of sulfated polysaccharides were correlated with increasing sulfate contents and DS of products [10]. Collectively, our results revealed that the sulfated EPS reliably increase the bio-activities of EPS extracted from O. sinensis culture broth.…”
Section: Antioxidant Of Sulfated Eps From O Sinensissupporting
confidence: 92%
“…and sulfate contents, in which antioxidant activity of sulfated derivatives were correlated with increasing sulfate contents, but decreasing M.W. [2,10]. Currently, sulfated modification of polysaccharides was performed by a variety of various methods, including oleum dimethylformamide, sulfur trioxide pyridine (SO3-Pyr), chlorosulfonic acid (CSA)-pyridine (Pyr) and aminosulfonic acid (ASA)-pyridine (Pyr) method [2,8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…CS-hEPS had higher scavenging ability due to its carboxymethyl, methoxyl, and sulfated groups, which is in agreement with the FTIR analysis and the sulfate content. ese groups were described in previous studies as free radical scavengers [50][51][52]. However, all these studies described the effect of chemically modified polysaccharides and so none of these works examined the combined effect of carboxymethyl, methoxyl, and sulfated groups on the bioactivity of polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, P. yezoensis produces compounds that protect against external factors, including environmental pollutants, stresses and UV radiation (22,23). P. yezoensis has antioxidant (24,25), antitumor (26,27) and anti-inflammatory activities (28,29), and protects against neuronal senescence (30,31), photoaging (22,23) and cytotoxicity (32,33).…”
Section: Pyp1-4 Peptide From Pyropia Yezoensis Protects Against Acetamentioning
confidence: 99%